2009
DOI: 10.1002/jssc.200800695
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of biomarkers and cell‐specific molecular signatures: Aptamers as capture agents

Abstract: RNA and DNA aptamers developed by systematic evolution of ligands by exponential enrichment (SELEX) have turned into important tools in diagnostics, research, and therapeutics. Unlike antibodies, high-affinity and specific aptamers identified through an in vitro selection process can be chemically modified to gain nuclease resistances in biological fluids and to extend their bioavailability in animals. Aptamers can be raised against virtually any target including those which are toxic or do not elicit any immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…This chemical stability allows apatmers to be reused numerous times. Aptamers are created by a process known as SELEX [133, 134]. There has been a recent emerging interest in using aptamers for various proteomics applications as selection agents [135, 136].…”
Section: Aptamer Assaysmentioning
confidence: 99%
“…This chemical stability allows apatmers to be reused numerous times. Aptamers are created by a process known as SELEX [133, 134]. There has been a recent emerging interest in using aptamers for various proteomics applications as selection agents [135, 136].…”
Section: Aptamer Assaysmentioning
confidence: 99%
“…Aptamers are able to identify individual epitopes within a complex mixture of potential targets and can also be used for ligand-mediated target purification (Nery et al, 2009, Ulrich and. It has been demonstrated that aptamers evolved against human membrane proteins bind specifically to previously unidentified target proteins (Morris et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…These unique binding features will help detect minimal differences in molecular signatures of stem cells and differentiated cells more precisely. 57 Aptamers could be bound to polymeric matrices or magnetic beads potentiating the affinity of the nanoparticle conjugates, diminishing the amount of magnetic markers required in large scale separation, improving current technologies and reducing the costs associated with increased amount of antibodies. 58 …”
Section: Challenges and Future Trendsmentioning
confidence: 99%